Digital services taxes: Multilateral and unilateral efforts and an overview of recent economic models - Renato E. Reside (University of the Philippines, School of Economics (UPSE), 2022)
This paper aims to describe the state of multilateral and unilateral efforts to tax digital services; summarize the state of economic analysis on digital services taxes; and provide an overview of where the Philippines stands in relation to other countries in digital service taxation. On-going efforts by other countries on digital taxation may have an impact on tax structure in the Philippines. The Philippines is currently drafting a law imposing VAT on these services, which is overdue and which may still be refined in some ways, but rationales exist as well for proposing other digital service taxes (DSTs), especially on revenue streams of large nonresident digital platforms. To do this, the country must update its tax laws further to account for the peculiarities of digital businesses. Economic models that explore the impact and incidence of DSTs are in nascent stages of development, but offer good insight for policymakers. The key is to recognize that digital platforms are 2-sided markets. In such markets, users on one side of the market can create value for participants on the other side. Digital platforms can capitalize on network externalities created by both sides (for instance, among users and advertisers) as well as scale economies and earn location-specific rents, which is one basis for DST taxation. Given these traits of 2-sided digital markets, traditional outcomes of taxation in one-sided market models may not apply. The paper ends by discussing open and partially addressed policy questions that need to be resolved soon.
Keywords: H2; H22; K34; 330; Digital service taxation; two-sided markets; taxation; tax law